Clinical studies of the Tildox AVZ complex drug efficacy in respiratory and gastrointestinal pathologies of young pigs caused by opportunistic microflora - Engashev Sergey V. (EDP Sciences, 2021)
This publication provides a study of the efficacy of Tildox AVZ (a combined formulation of doxycycline and tylosin) in non-specific bacterial respiratory and gastrointestinal pathologies in piglets. The study population included 70 piglets with respiratory and gastrointestinal pathologies randomized into 6 groups. The effects of investigational drug used according 3-day or 5-day regimen were assessed using clinical examination, as well as bacteriological, blood count and blood chemistry lab tests. The investigational drug (Tildox AVZ) was safe for target animals and had no adverse effects, showed a similar species specificity and efficacy on the respiratory and gastrointestinal flora in piglets vs. the reference drug (Gentamicin) and allows achieving a beneficial clinical effect in respiratory and gastrointestinal diseases caused by opportunistic microflora. A significant clinical effect is achieved by Day 4 in gastrointestinal pathology and by Days 6-7 in respiratory pathology. Moreover, the control group with gastrointestinal pathology had no changes in the most of the parameters vs. baseline even on Day 7. Tildox AVZ had no adverse effects on blood count and blood chemistry parameters; on the contrary, for a number of parameters, a trend towards normalization was noted. The investigational drug was at least equivalent to the reference one (Gentamicin) and can be used for both respiratory and gastrointestinal disorders caused by the non-specific opportunistic bacterial microflora.